IMPLEMENTASI MEDIA VIDEO PEMBELAJARAN DALAM MENINGKATKAN PERKEMBANGAN BAHASA ANAK USIA DINI USIA 3-4 TAHUN DI KELOMPOK BERMAIN PELITA SAMARINDA - Heppy Liana; Nurhaliza Afifah (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
The implementation of learning in the Pelita play group has 13 students and among them there are 6 children who cannot speak clearly, this can be seen when the child is asked to convey or express his feelings, but when holding a smartphone the child shows his interest. Aiming to find out the learning video media can improve the language of early childhood aged 3-4 years in the Pelita playgroup and find out the strategy of learning video media in improving the language of early childhood aged 3-4 years in the Pelita playgroup. This research uses a descriptive qualitative approach method with data collection through observation, interviews and documentation. Activities to improve children's language development are stimulated by a variety of varied media but researchers choose to take learning video media as a medium that can improve early childhood language skills. The process of activities carried out to improve the language development of early childhood aged 3-4 years in the Pelita play group experiences the stages of the process of improvement well. In providing activities using learning video media during learning, children's language skills began to increase every meeting by 81%.